SERUM lactate dehydrogenase level in hodgkin's disease relationship to certain features at the time of diagnosis - AL- Hadithi, mutaz F.; Al-Khazraji, Fuad M.; AL-Khazraji, Khalid A. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: